Investigation of heat transfer enhancement in impinging jet-dimpled-protruded solar air heaters - Waqas, Muhammad; Raheem , Aneeq; Siddique , Waseem; Waheed, Khalid; Zaki, Muhammad (Archive of Mechanical Engineering, 2026)
Solar energy is a source of renewable energy and is considered a clean, convenient, sustainable, safe, abundant, and economical source. Solar Air Heaters (SAHs) are one of the applications of solar energy. SAH has a wide variety of applications but has low thermal efficiency. This low thermal efficiency is due to the low thermal capacity of the air, and the poor process of heat transfer between the absorbing plate channel and air. With the aim to improve thermal efficiencies, the novel dimple/protrusion surfaces have been incorporated onto the 307 × 212 mm aluminum absorbing plate. A 3 × 3 array of 5 mm impinging jets is used to further decrease the temperature of the plate. A set of five different plate configurations, i.e., smooth, dimpled, dimpled-protruded, protruded-dimpled, and protruded configurations are simulated by using the experimentally validated Computational Fluid Dynamics (CFD) model. The values of heat transfer enhancement, pressure drop, and Thermal Performance Factor were evaluated from the CFD study. The protruded plate is selected as the best plate configuration, based on the Thermal Performance Factor. An overall improvement of 33.5% is observed in the current research work, as compared to the smooth configuration. Hence promising is the augmentation.